A flexible microfluidic strategy to generate grooved microfibers for guiding cell alignment. (21st June 2021) - Zhao, Mengqian; Liu, Haitao; Zhang, Xu; Wang, Hui; Tao, Tingting; Qin, Jianhua
Abstract : A flexible microfluidic strategy to generate grooved microfibers relies on in situ gelling of different concentrations of alginate as anisotropic scaffolds for guiding cell alignment. Abstract : Hydrogel microfibers are widely applied in tissue engineering and regenerative medicine due to their tunable morphology, componential anisotropy, and good biocompatibility. Specifically, grooved microfibers with unique advantages can facilitate cell alignment for mimicking the microstructures of myobundles. Herein, a microfluidic spinning system is proposed for flexibly generating grooved microfibers relying on the volume change after ionic crosslinking of sodium alginate (NaA) with different concentrations. In the system, multiple parallel channels are integrated into a flow-focusing microchip and NaA with various concentrations is introduced into the respective channels for fabricating well-defined microfibers. The size and shape of the fibers are tuned by the viscosity and concentration of the NaA solution, as well as the flow rates of NaA and calcium chloride (CaCl2 ) in a controllable manner. Moreover, the grooved fibers with heterogeneous components can be generated via co-spinning gelatin methacrylate (GelMA) and NaA to form interpenetrating polymer networks (IPNs). The microfibers with heterogeneous IPNs are successfully used as anisotropic scaffolds for the 3D culture of muscle cells (C2C12). The muscle cells grown on the microfibers exhibited good viability and ordered alignment, indicating the good biocompatibility and orientational function of the heterogeneous fibers. The proposed approach is flexible and controllable, holding potential in replicating various aligned microstructures in vivo, such as bundles of nerves and blood vessels.